Multitasking - Anzelika Zaiceva (Institute of Labor Economics (IZA), 2022)
This chapter reviews economic studies on multitasking in household production. Whereas multitasking or task juggling in the workplace has been analyzed more widely, economic literature on multitasking in a household is relatively scarce. The chapter first provides relevant measures of such multitasking activities, discusses time diary data, and presents some empirical facts employing Harmonized European Time Use Survey data. It then reviews theoretical and empirical contributions to this topic, focusing on childcare, food consumption, and remote work. It also reviews the determinants of multitasking and identifies the factors that are more likely to affect these activities. In addition, it discusses multitasking by certain groups, such as ethnic minorities and children. Finally, it offers policy implications and suggestions for future research.
Keywords: D13; J22; J16; 330; household production; multitasking; simultaneous activities; time use